2004
DOI: 10.1172/jci19933
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral actions of somatostatin on the growth hormone–IGF-I axis

Abstract: Somatostatin (SRIF) analogs provide safe and effective therapy for acromegaly. In a proportion of patients, however, SRIF analogs may lead to discordant growth hormone (GH) and IGF-I suppression, which suggests a more complex mechanism than attributable to inhibition of GH release alone. To elucidate whether SRIF acts peripherally on the GH-IGF-I axis, we showed that rat hepatocytes express somatostatin receptor subtypes-2 and -3 and that IGF-I mRNA and protein levels were suppressed in a dose-dependent manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 60 publications
(27 reference statements)
3
83
0
2
Order By: Relevance
“…In light of the activation of transcription factors such as C/EBPs and Stat3 in all the trout SSTR-expressing cells and the observed linakge between ERK and PI3K/Akt and these transcription factors in mammalian systems (Chung 1997, Schrem et al 2004, Cui et al 2008, it is possible that alterations in the activity state of C/EBPb and Stat3 and the modulation of GHR and IGF1 transcription may underlie SS inhibition of GHR and IGF1 expression in trout liver cells. SS-induced activation of Stat5 also was linked to reduced hepatic GH binding in rat hepatocytes (Murray et al 2004). It was shown recently that increased ERK and Akt activation was attended by increased p53 activation (Tanel & Averill-Bates 2007), suggesting that SSTR1A/ SSTR2-triggered ERK and/or PI3K/Akt activation of p53 may underlie, at least in part, SS-induced inhibition of IGFR expression in native gill filaments of trout.…”
Section: Discussionmentioning
confidence: 91%
“…In light of the activation of transcription factors such as C/EBPs and Stat3 in all the trout SSTR-expressing cells and the observed linakge between ERK and PI3K/Akt and these transcription factors in mammalian systems (Chung 1997, Schrem et al 2004, Cui et al 2008, it is possible that alterations in the activity state of C/EBPb and Stat3 and the modulation of GHR and IGF1 transcription may underlie SS inhibition of GHR and IGF1 expression in trout liver cells. SS-induced activation of Stat5 also was linked to reduced hepatic GH binding in rat hepatocytes (Murray et al 2004). It was shown recently that increased ERK and Akt activation was attended by increased p53 activation (Tanel & Averill-Bates 2007), suggesting that SSTR1A/ SSTR2-triggered ERK and/or PI3K/Akt activation of p53 may underlie, at least in part, SS-induced inhibition of IGFR expression in native gill filaments of trout.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the suppressive effect of somatostatin on insulin secretion (13) may result in reduced hepatic IGF1 production, and hence lower serum IGF1 levels, in as much as insulin stimulates hepatic GHR synthesis and activity (30). Moreover, data from rodent studies show that somatostatin directly suppresses hepatic IGF1 production and possibly also the receptor-mediated clearance of GH (12), and a study in healthy human subjects indicates that somatostatin exerts GH-antagonistic effects directly in skeletal muscle in vivo (31). It has also been suggested that somatostatin may antagonize the suppressive effect of oral glucose on GH secretion (8), and it is worth noting that the difference in GH levels in our study was mainly present during the OGTT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, slightly elevated GH levels in the presence of normalized IGF1 levels may be an early predictor of disease recurrence (10), but cases of persistent disease despite very low GH levels (and elevated IGF1 levels) also exist (7,11). Furthermore, somatostatin acts not only at the pituitary level to suppress GH release, but also exhibits inhibitory effects on GH signaling and thus GH receptor (GHR)-mediated clearance of GH (12). In addition, somatostatin suppresses insulin secretion (13), which may lower hepatic IGF1 production and hence also the circulating levels of IGF1 (14).…”
Section: Introductionmentioning
confidence: 99%
“…They inhibit pituitary GH release and sst2 and sst5 are the subtypes primary involved in this effect. They also inhibit hepatic GH-induced IGF-I production via sst2-and/or sst3-mediated activation of a tyrosine phosphatase leading to dephosphorylation of STAT5b and to a decrease in IGF-I gene transcription (Murray et al, 2004).…”
Section: Indirect Antitumor Effects Of Somatostatinmentioning
confidence: 99%
“…Tumor angiogenesis is essential for tumor growth, invasion and metastasis. Several experimental results indicate that somatostatin analogs inhibit angiogenesis in vitro and in vivo (Murray et al, 2004). Overexpression of peritumoral vascular somatostatin receptors with high-affinity for sst2-preferring analog octreotide has been reported in human primary colorectal carcinomas, small cell lung carcinoma, breast cancer, renal carcinoma and malignant lymphoma.…”
Section: Indirect Antitumor Effects Of Somatostatinmentioning
confidence: 99%